Relationships of comorbidities and old age with postoperative complications of head and neck free flaps: A review. Issue 12 (December 2016) - Hwang, Kun; Lee, Jin Pyo; Yoo, Si Yoon; Kim, Hun
Summary: The aim of this study was to determine the relationships between free flap complications and old age or comorbidities. In a PubMed and Scopus search, the search terms (1) free flap OR microvascular anastomosis AND (2) elderly OR old age AND (3) complications OR comorbidity OR co-morbidity were used. Among the 62 full-text articles from 241 abstracts, 31 papers without sufficient content were excluded and 10 mined papers were added. Subsequently, 41 papers were reviewed. Overall complication rates of free flap increased significantly with age ( p  < 0.001; y  = 0.457 x  + 13.464; 40.9% at 60 years, 45.5% at 70 years, and 50.0% at 80 years). Flap survival rates increased significantly ( p  < 0.001; y  = 0.025 x  + 93.876). Donor site complication rates also increased significantly with age ( p  < 0.001; y  = 1.238 x  − 63.700; 10.9% at 60 years, 23.0% at 70 years, and 35.3% at 80 years). The Kaplan–Feinstein index (KFI, OR = 7.944, 9.563), the Adult Comorbidity Evaluation-27 (ACE-27, OR = 5.854), the American Society of Anesthesiologists score (ASA, OR = 4.397), and the Index of Coexistent Diseases score (ICED, OR = 3.584) had statistically significant impacts on flap survival ( p  < 0.05). Diabetes (OR = 4.562) and chronic obstructive pulmonary disease (OR = 2.300) had statistically significant negative impacts on the flap survival rate ( p  < 0.05). Elderly patients had significantly higher Charlson Comorbidity Index (CCI) and ASA scores ( p  < 0.001). Similarly, elderly patients exhibited a significantly higher prevalence of dementia ( p  < 0.001) and use of aspirin at the time of surgery ( p  < 0.001). On the basis of these results, we suggest that the incidence of complications is directly related to the preoperative medical condition of an individual patient rather than to age.